Dialectics Dance Ritual in Wanara Parisuka in Talunkacang Kreo Cave Semarang Central Java - Ekowati, Yunik; Sunarto, Sunarto; Malarsih, Malarsih (Universitas Negeri Semarang, 2019)
Wanara Parisuk dance is one of the traditional arts are contained in a series of ritual offerings Rewanda and entertainment in Kreo cave Semarang. Derived from the word â€œ Wanaraâ€ which means monkey, â€œParisukaâ€ means having fun. Dance Wanara Parisuka used as a ritual and entertainment interests. Objective to study the dialectic Dance Wanara Parisuka (study: ritual and entertainment). The method used in this study is a qualitative ethnographic approach. Data collection techniques are observation, observation, interviews, document study.Mechanical validity of data used triangulation techniques and data analysis techniques that follow an interactive model analysis phase.Dance research results Wanara Parisuka there are two kinds of functions: as a ritual and as entertainment. The findings are important as ritual offerings in Rewanda Dance Ritual Wanara Parisuka presented at the peak of the ritual. Overall findings as entertainment is to entertain and attract public interest, dancers invite the audience to dance together, to entertain the audience. In the dialectic Dance Wanara Parisuka there are three stages namely; thesis (function according to each), antithesis (rejection, both have different roles and can not be mixed), the synthesis of (mutual influence, and biting for togetherness and strategic importance attract the interest of visitors).